Otsenka adaptatsionnykh reaktsii sportsmenov-lyzhnikov na etapakh podgotovki - Kozyrev, O. A.; Bogatchev, R. S.; Dubenskaya, L. I.; Isayeva, S. A.; Chamtsova, G. B.; Kryuchkov, S. A.; Samorodskaya, I. S. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of this study was to reveal the dynamics of the cardio-vascular system's indices in connection with the non-specific morphological parameters' adaptation of elite skiers at various stages of their training process. The elite skiers (13 males ages 18,7) acted as subjects of the research. The through-esophagus electro-physiological heart's examination, the cardiointervalography and echocardiography as well as the harmonic homeostasis and morphological content of a peripheral blood had been used. It had been shown that the change of the training stage of athletes - skiers leads to the certain transformations in the electro-physiological properties of a heart's conducting ways and the endocrine system's functional activity.